2020
DOI: 10.33448/rsd-v9i9.6990
|View full text |Cite
|
Sign up to set email alerts
|

Assistência fisioterapêutica ao paciente com HIV/SIDA em um hospital de referência do estado da Paraíba

Abstract: Este estudo teve como objetivo analisar a assistência fisioterapêutica em pacientes com HIV/SIDA em um hospital de referência no estado da Paraíba no período de julho de 2017 a julho de 2018. A amostra envolveu 79 prontuários e 17 fisioterapeutas, tratou-se de  um estudo retrospectivo e prospectivo transversal, de caráter exploratório/descritivo com abordagem quantitativa e qualitativa. Os critérios de inclusão para inclusão dos prontuários foram de ter registros da assistência fisioterapêutica, ter idade entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 9 publications
0
2
0
6
Order By: Relevance
“…In cases of neurological sequelae, rehabilitation through a multidisciplinary approach, including physical therapy, should be prioritized, aiming to minimize, or even revert, possible disabilities caused by disease; moreover, interventions leading to an individual's functional capacity and general quality of life are of great importance (76)(77)(78). Physical therapy is essential in cases of demyelinating/opportunistic diseases, easing the progression of sequelae and preserving the musculoskeletal tissue in people living with HIV/AIDS (79). Demyelinating opportunistic diseases present a similar spectrum of symptoms that mainly involve motor deficits such as weakness, contractures, gait and balance disorders, among others (24,56,(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of neurological sequelae, rehabilitation through a multidisciplinary approach, including physical therapy, should be prioritized, aiming to minimize, or even revert, possible disabilities caused by disease; moreover, interventions leading to an individual's functional capacity and general quality of life are of great importance (76)(77)(78). Physical therapy is essential in cases of demyelinating/opportunistic diseases, easing the progression of sequelae and preserving the musculoskeletal tissue in people living with HIV/AIDS (79). Demyelinating opportunistic diseases present a similar spectrum of symptoms that mainly involve motor deficits such as weakness, contractures, gait and balance disorders, among others (24,56,(78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…Physical therapy is essential in cases of demyelinating/opportunistic diseases, easing the progression of sequelae and preserving the musculoskeletal tissue in people living with HIV/AIDS (79). Demyelinating opportunistic diseases present a similar spectrum of symptoms that mainly involve motor deficits such as weakness, contractures, gait and balance disorders, among others (24,56,(78)(79)(80). Several studies have already shown the improvement of balance deficits, strength gain, and maintenance of muscle tissue and general functional performance through rehabilitation by a multidisciplinary team (81,82).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, ser uma pessoa que vivem com HIV/AIDS não é o mesmo que ter a SIDA (2). Existem muitos indivíduos com essa condição que vivem sem desenvolver a doença e que são assintomáticos (1)(2)(3). Todavia, podem transmitir o vírus de diversas formas, como por exemplo, exposição a relações sexuais desprotegidas e compartilhamento de materiais perfurocortantes (4).…”
Section: Introductionunclassified
“…Todavia, podem transmitir o vírus de diversas formas, como por exemplo, exposição a relações sexuais desprotegidas e compartilhamento de materiais perfurocortantes (4). Além disso, existe a forma de transmissão vertical (TV), que é quando a mãe passa o vírus para o bebê, seja no momento do parto ou durante a amamentação (1)(2)(3)(4). A TV é uma das principais causas de infecções pediátricas pelo HIV, sendo responsável por mais de 90% dos casos diagnosticados (3)(4).…”
Section: Introductionunclassified
See 1 more Smart Citation